2015
DOI: 10.1007/s00167-015-3942-8
|View full text |Cite
|
Sign up to set email alerts
|

Classification and diagnosis of acute isolated syndesmotic injuries: ESSKA-AFAS consensus and guidelines

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 62 publications
2
97
0
15
Order By: Relevance
“…5 The European Society of Sports Traumatology, Knee Surgery and Arthroscopy-Ankle and Foot Associates (ESSKA-AFAS) recommends the clinical tests: tenderness on palpation over the anterior tibiofibular ligament, the fibular translation test and the Cotton test. 38 Those used in the current study included ability to hop, tenderness to palpation over the syndesmosis, external rotation test and the squeeze test, as suggested by Smam et al 10 In all cases, the injury was observed by medical professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The European Society of Sports Traumatology, Knee Surgery and Arthroscopy-Ankle and Foot Associates (ESSKA-AFAS) recommends the clinical tests: tenderness on palpation over the anterior tibiofibular ligament, the fibular translation test and the Cotton test. 38 Those used in the current study included ability to hop, tenderness to palpation over the syndesmosis, external rotation test and the squeeze test, as suggested by Smam et al 10 In all cases, the injury was observed by medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…38 Further classification would be valuable in determining the grade of injury according to severity and aid prognosis and management planning. Causal relationships and predictions between preseason status, previous injury, training and classification or outcome postsurgery, including RTP, could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…According to the West Point Ankle Grading System, three grades of syndesmotic injuries can be distinguished 1. A grade I injury involves a partial tear to the anterior inferior tibiofibular ligament (AITFL) with a normal ankle radiograph.…”
Section: Introductionmentioning
confidence: 99%
“…Sprain Grade System (2,(7)(8)(9) , que establece 3 grados de inestabilidad tibiofibular basándose en hallazgos clínicos y de radiografía simple (Tabla 1); sin embargo, no queda clara la diferencia entre los grados I y II, lo que puede dar lugar a dudas en la práctica clínica (9) . La European Society of Sports Traumatology, Knee Surgery and Arthroscopy-Ankle and Foot Associates (ESSKA-AFAS), tras una revisión de la bibliografía, define la lesión aislada de la sindesmosis tibiofibular distal como la lesión de uno o más ligamentos de la sindesmosis, asociada o no a afectación del complejo ligamentoso deltoideo, y la clasifica en función del tiempo de evolución como aguda, cuando presenta menos de 6 semanas, subaguda entre 6 semanas y 6 meses, y crónica con una evolución de más de 6 meses, siendo estos plazos determinantes a la hora de establecer el tratamiento más adecuado en cada caso (9) .…”
unclassified